Drug resistance associated properties of blasts subpopulations with different CD34 expression in childhood acute lymphoblastic leukemia (ALL) - Shman, T.V.; Fedasenka, U.U.; Savitski, V.P.; Kustanovich, A.M.; Aleinikova, O.V. (Experimental Oncology, 2011)
Aim: The objective of this study was to investigate expression of drug resistance associated genes in CD34+ and CD34- leukemic subpopulations in childhood acute lymphoblastic leukemia (ALL). Methods: ALL samples with heterogeneous CD34 expression were separated into CD34-positive and CD34-negative subpopulations and mRNA levels of MDR1, LRP , BCRP and BCL-2 genes were compared. Results: BCL-2 gene expression levels did not differ significantly between CD34+ vs CD34− subpopulations in most analyzed ALL cases. Oppositely, MDR1 gene had >two-fold differences in expression levels between subpopulations in the majority of ALL cases. In T-lineage ALL CD34− fractions had increased level of BCRP and LRP genes in comparison with CD34+ ones whereas in most of B-lineage ALL expression of these genes did not differ. Conclusion: It was not found the unique pattern of resistance related genes expression in CD34+ vs CD34− subpopulations. However, in majority of studied pediatric ALL cases with CD34 heterogeneous expression one of subpopulations (positive or negative) could have an advantage for survival through elevated expression of drug resistance related genes.